Differential expression profile of plasma exosomal microRNAs in chronic rhinosinusitis with nasal polyps. Issue 12 (June 2022) - He, Shuai; Wu, Jun; Han, Demin; Li, Yunchuan; Wang, Tong; Wei, Hongzheng; Pan, Yangwang; Zang, Hongrui
Exosomes mediate inflammation and immune responses. The aim of the study was to examine the expression profiles of plasma exosomal microRNAs (miRNAs) and analyze their target gene functions in participants with chronic rhinosinusitis with nasal polyps (CRSwNP). We measured plasma exosomal miRNAs in five patients with CRSwNP and five controls. Transcripts per million (TPM) was used to assess miRNAs expression and the Benjamini–Hochberg procedure was employed for multiple comparisons correction. Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene ontology (GO) analyses revealed biological annotation and functional prediction of target genes. Compared with controls, we found that 159 exosomal miRNAs were differentially expressed by miRNA sequencing in CRSwNP. The top three upregulated miRNAs were novel_miR_677, novel_miR_1037, and novel_miR_79, while the top three downregulated miRNAs were novel_miR_192, novel_miR_1022, and novel_miR_4. The target functions in the GO and KEGG analyses included axon guidance, extracellular matrix (ECM)–receptor interaction, protein digestion and absorption, the calcium, the Hippo, the Notch, the ErbB, the cAMP signaling pathway, and focal adhesion. This study describes the dissection of plasma exosomal miRNA profiling in CRSwNP. Our findings may provide a certain basis for further mechanism research and exploration of diagnostic values.